Toll-Like Receptor 4 Knockout Mice Are Protected against Endoplasmic Reticulum Stress Induced by a High-Fat Diet - Pierre, Nicolas (Public Library of Science, 2013)
The purpose of this study was to investigate whether toll-like receptor 4 (TLR4) is implicated in the development of endoplasmic reticulum stress (ER stress) observed after a high-fat diet (HFD) in liver, skeletal muscle and adipose tissue. TLR4(−/−) and C57BL/6J wild-type mice (WT) were fed with chow or HFD (45% calories from fat) during 18 weeks. An oral glucose tolerance-test was performed. The animals were sacrificed in a fasted state and the tissues were removed. TLR4 deletion protected from body weight gain and glucose intolerance induced by HFD whereas energy intake was higher in transgenic mice suggesting larger energy expenditure. HFD induced an ER stress in skeletal muscle, liver and adipose tissue of WT mice as assessed by BiP, CHOP, spliced and unspliced XBP1 and phospho-eIF2α. TLR4(−/−) mice were protected against HFD-induced ER stress. Then, we investigated the main signaling downstream of TLR4 namely the NF-κB pathway, expecting to identify the mechanism by which TLR4 is able to activate ER stress. The mRNA levels of cytokines regulated by NF-κB namely TNFα, IL-1β and IL-6, were not changed after HFD and phospho-IκB-α (ser 32) was not changed. Our results indicate that TLR4 is essential for the development of ER stress related to HFD. Nevertheless, the NFκ-B pathway does not seem to be directly implicated. The reduced fat storage in TLR4(−/−) mice could explain the absence of an ER stress after HFD.